KEBIJAKAN PEMBATASAN PENGGUNAAN TELEPON SELULER DI SEKOLAH MENENGAH KOTA PADANG - Seprigo Rizkan; Indra Rahmat; Asril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mobile phone use in schools can support learning, but it may also disrupt students’ concentration, discipline, and social interaction. This study aimed to understand the implementation of a mobile phone restriction policy and describe student and parent responses at SMA Negeri 12 Padang and SMK Negeri 5 Padang. The policy was based on Circular Letter No. 100.3.4.4/3240/SEK/DISDIK-2025 issued by the West Sumatra Provincial Education Office. This study employed a qualitative descriptive approach. Data were collected through semi-structured interviews, observations, and documentation involving 18 informants from school leadership, teachers, students, and parents. The findings show that both schools implemented the policy through different mechanisms. SMA Negeri 12 Padang had previously used a centralized classroom-box storage system, while SMK Negeri 5 Padang relied more heavily on subject-teacher supervision. Policy implementation was constrained by inadequate storage facilities, inconsistent supervision, the absence of a designated task force, and irregular evaluation and reporting. Student and parent responses indicated general acceptance of the restriction’s purpose, while also emphasizing the need for access during learning and emergencies, secure device storage, and accessible family communication. The findings indicate that policy acceptance is influenced by clear and consistent implementation, secure storage, and accommodation of learning needs.